1986
DOI: 10.1002/macp.1986.021870714
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the free radical copolymerization of diethyl maleate with methyl methacrylate

Abstract: The kinetics of the free radical copolymerization of diethyl maleate (M1 ) with methyl methacrylate (M2) was studied in bulk at 60°C with azoisobutyronitrile (AIBN) as initiator. The reactivity ratios of the system were determined by means of H NMR spectroscopy. The obtained values show that diethyl maleate is not only unable to homopolymerize (rI2 = 0) but also displays a very low tendency to incorporate in the polymer chain (rZ1 = 370) under the present conditions. Molecular weight measurements showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…19 For the same reason, MAH, after reacting with the primary radicals derived from the initiator, could induce homopropagation (thereby generating not-grafted oligomers from MAH), thereby reducing the amount of monomer available for the reaction with the macroradicals of the polyolefins, reducing FD, and increasing the probability of crosslinking. This is probably not valid for DEM; indeed, the reactivity ratios determined for the copolymerizations of the DEM/ methylmethacrylate 20 and DEM/styrene 21 systems showed that DEM participated only to a very small extent in the propagation step.…”
Section: Methodsmentioning
confidence: 88%
“…19 For the same reason, MAH, after reacting with the primary radicals derived from the initiator, could induce homopropagation (thereby generating not-grafted oligomers from MAH), thereby reducing the amount of monomer available for the reaction with the macroradicals of the polyolefins, reducing FD, and increasing the probability of crosslinking. This is probably not valid for DEM; indeed, the reactivity ratios determined for the copolymerizations of the DEM/ methylmethacrylate 20 and DEM/styrene 21 systems showed that DEM participated only to a very small extent in the propagation step.…”
Section: Methodsmentioning
confidence: 88%
“…A series of at least 14 papers [200][201][202][203][204][205][206][207][208] have been published dealing with the synthesis of telechelic polymers or block copolymers from the radical polymerization of various vinyl monomers with substituted l,l,2,2-tetraphenyl ethanes. These aromatic compounds, known for over a century [209], are efficient in radical polymerization [201,210].…”
Section: Substituted Tetraphenyl Ethanesmentioning
confidence: 99%
“…These aromatic compounds, known for over a century [209], are efficient in radical polymerization [201,210]. They behave as both initiators and terminating agents [200] that can be involved in living radical polymerization as illustrated in the following reaction: Rl = H or CH3, R 2 = C6H 5, or RI= CH 3 and R2= CO2R R= H, CH 3, nC4H 9, tf4H 9, CH2C6H 5 .…”
Section: Substituted Tetraphenyl Ethanesmentioning
confidence: 99%
See 2 more Smart Citations